TEMBANG MACAPAT SEBAGAI SUMBER IDE GENDING-GENDING KARYA KI NARTOSABDO - Mr. Suparto (SELONDING, 2012)
Ki Nartasabda used Sekar Macapat as one of the inspirations in creating gamelan ensemble compositions. The expression of the Javanese traditional poetry was applied in the composition elements such as bawa, gerongan, and lelagon. Therefore, the elements were related to different ambiences of the traditional songs and cakepan did not completely follow the rimes of the Javanese poetry and also cengkok in the Sekar Macapat. The Sekar Macapat in the gamelan ensemble compositions created by Ki Nartasabda was expressed implicitly and explicitly in the bawa, the gerongan and the lelagon. The examples of the gamelan ensemble compositions were contained in the forms of Bawa Sekar Mijil, Ladrang Pocung, Lelagon Gambuh Pangatag, Lancaran Wira-wiri, and Lancaran Begadhang (Sinom). Keywords: Macapat, Gending, Compositions